2022
DOI: 10.3390/microorganisms10081533
|View full text |Cite
|
Sign up to set email alerts
|

New Variants of Pseudomonas aeruginosa High-Risk Clone ST233 Associated with an Outbreak in a Mexican Paediatric Hospital

Abstract: Recent multidrug resistance in Pseudomonas aeruginosa has favoured the adaptation and dissemination of worldwide high-risk strains. In June 2018, 15 P. aeruginosa strains isolated from patients and a contaminated multi-dose meropenem vial were characterized to assess their association to an outbreak in a Mexican paediatric hospital. The strains were characterized by antibiotic susceptibility profiling, virulence factors’ production, and biofilm formation. The clonal relationship among isolates was determined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
4
1
Order By: Relevance
“…The observations of potential high-risk and locally distributed clones underscore the relevance of continued inspection of the population structure in clinical settings in different parts of the world. Although previous studies had showed that high-risk clones were predominant among multidrug-resistance strains (del Barrio-Tofiño et al, 2020;Hu et al, 2021;Teo et al, 2021;Aguilar-Rodea et al, 2022), we found that 50/212 isolates (23.58%) belong to the 18 previously reported high-risk clones, and that the remaining isolates showed high diversity together with other reported STs in all strains.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The observations of potential high-risk and locally distributed clones underscore the relevance of continued inspection of the population structure in clinical settings in different parts of the world. Although previous studies had showed that high-risk clones were predominant among multidrug-resistance strains (del Barrio-Tofiño et al, 2020;Hu et al, 2021;Teo et al, 2021;Aguilar-Rodea et al, 2022), we found that 50/212 isolates (23.58%) belong to the 18 previously reported high-risk clones, and that the remaining isolates showed high diversity together with other reported STs in all strains.…”
Section: Discussioncontrasting
confidence: 76%
“…One ST298 isolate and one ST446 isolate, both with MDR/XDR phenotype, were identified in different hospitals. In some regional research projects, the clonal diversity of P. aeruginosa is much lower among multidrug-resistant isolates (del Barrio-Tofiño et al, 2020;Hu et al, 2021;Teo et al, 2021;Aguilar-Rodea et al, 2022). This is not entirely the case among our MDR subsets from 2018-2020.…”
Section: Discussionmentioning
confidence: 78%
“…However, the association between ICs and STs, which could make the assignment easier, was established by computational, rather than molecular, methods, with the introduction of the eBURST algorithm, which divides an MLST data set of any size into groups of related isolates and CCs and predicts the founding (ancestral) genotype of each CC [ 58 ]. This algorithm was widely used for defining CCs of various bacterial species [ 59 , 60 ], and it was later applied to associate A. baumannii ICs with the corresponding dominant STs from both the Pasteur and Oxford schemes developed [ 61 ].…”
Section: International Clone (Ic) Definitions Attributes and Propertiesmentioning
confidence: 99%
“…The highly variable genome empowers MDR P. aeruginosa to survive and disseminate successfully by clonal expansion in addition to the acquisition of various resistance genes [37]. Therefore, the genetic diversity of P. aeruginosa helped the global dispersion of high-risk clones, such as ST235, ST111, ST233, ST244, ST357, ST308, ST175, ST277, ST654 and ST298 [38,39]. Most of the high-risk clones have metallo β-lactamase (MBL) carbapenemase production; however, ST111 and ST235 have multiple carbapenemase genes besides MBL [40].…”
Section: Introductionmentioning
confidence: 99%